탄소나노튜브 트랜지스터 제작 - 박용욱; 윤석진 (한국전기전자재료학회, 2007)
We fabricated field-effect transistor based carbon nanotubes(CNTs) directly grown by thermal chemical vapor deposition(CVD) and analyzed their performance. The Ethylene (C2H4), hydrogen(H2) and Argon(Ar) gases were used for the growth of CNTs at 700 ℃. The growth properties of CNTs on the device were analyzed by SEM and AFM. The electrical transport characteristics of CNT FET were investigated by I-V measurement. Transport through the nanotubes is dominated by holes at room temperature. By varying the gate voltage, we successfully modulated the conductance of FET device by more than 7 orders of magnitude.